Development of flash-based learning media to improve critical thinking ability of grade VII middle school students - Lutfi Marfuah; Yesi Franita; Zuida Ratih Hendrastuti (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
The development of technology is certainly very helpful for developing the world of education. But, many learning activities are carried out using conventional methods, namely lectures with books and blackboards which result in boring learning and poor critical thinking skills on the initial test. The purpose of this study was to determine the level of validity, practicality, and effectiveness of interactive media used to improve critical thinking skills. Research using the ADDIE model shows that the developed interactive media has very valid criteria based on the media validator's assessment of 97.67 and the material validator's assessment of 57 categories. The media developed with very practical criteria based on student practicality questionnaires of 85.06% and teacher practicality questionnaires of 96% categories. In addition, the developed media obtained an effectiveness score of 90.63% based on the posttest of critical thinking skills. From the above findings, it can be concluded that interactive media can be used validly, practically, and effectively to improve critical thinking skills.